If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x = x + -2 Reorder the terms: 8x = -2 + x Solving 8x = -2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8x + -1x = -2 + x + -1x Combine like terms: 8x + -1x = 7x 7x = -2 + x + -1x Combine like terms: x + -1x = 0 7x = -2 + 0 7x = -2 Divide each side by '7'. x = -0.2857142857 Simplifying x = -0.2857142857
| (-9x-3).2/3 | | r^2-16r+15=0 | | 34x+3+96+59x+75=360 | | 9k+3=12k | | 130+48+14x=360 | | 2w+7=16 | | 42j+19j-18=28 | | 9x-3+30=90 | | n^2-10n-39=0 | | (2x-1)(x+8)=2x^2+15x-8 | | 5sin^2a-5sin^4a=5cos^2a-5cos^4a | | 8+14x-7=7x+56-4x | | Z-7=1+2Z | | 6t=-21 | | 2Y+9=10Y | | 6x+9=rx+t | | x(90-x)=18 | | -22.5=7k-5.5k | | x+60-y-10=180 | | 3=x/-3-1 | | 2*(7/4)^2-7(7/4)-4 | | 15=7x-5(2x+3) | | 39=3(x+2) | | -3n-4+2n=-27 | | 29+12x=173 | | 198=-6(-6-3) | | 12x-20=-4x-16 | | 8k+12=52 | | -7x-28=-98 | | (2x-6)(2x-3)=0 | | 157*=2 | | log[3](2x+1)=2 |